Heidegger’s Existential Diagnosis and Bonaventure’s Positive Existential Remedy: Using Hermeneutics to Address the Problem of Anxiety over Intellectual Finitude - Lo, Jonathan Chung-Yan (Religions, 2023)
In today’s postcritical environment, the philosophical disciplines have at times acquired a negative reputation for abstraction, relativity and impracticability. While indispensable to the modern university curriculum, the meaning and utility of the philosophical enterprise continues to register ambivalently in modern popular consciousness. In this article, I challenge this popular assumption with a case study in philosophical interpretation, by applying the hermeneutics of German existentialist Martin Heidegger (1889–1976) to issues of practical religious life. Within a life-context of anxiety over intellectual finitude and its ensuing projections, I demonstrate how the innovative sapiential reading of Christ by medieval Franciscan theologian Bonaventure of Bagnoregio (c. 1217–1274) supplies a productive intervention to ensure a new state-of-mind. This new state-of-mind arising from a new mode of understanding and being-in-the-world, amounts to a transmutation of the Heideggerian hermeneutic mode in the light of biblical truth. Bonaventure’s threefold way of Christological exegesis serves as a requisite framework in which to practically redeploy the Heideggerian way of understanding towards a positive existential end.